Nanofibras de carbono verticalmente alinhadas: estudo do crescimento por microscopia eletrônica de transmissão - Daniel Bretas Roa (2008)
This work is about the growth of vertically aligned Carbon Nanofibers -CNFs - grown by Plasma Enhanced Chemical Vapour Deposition - PECVD. Being so, a detailed study of catalyst particle is necessary and Transmission Electron Microscopy - TEM - is fundamental for this knowledge. Some analytical techniques associated to TEM were used: Bright and Dark Field Images; Selected Area Electron Diffraction - SAD; High Resolution Transmission Electron Microscopy - HRTEM. Additional techniques were also performed: Scanning Electron Microscopy - SEM; Mössbauer Spectroscopy; Energy Dispersive X-Ray Spectroscopy - EDS. Series of depositions optimizing the parameters of CNFs growth using Ni as catalyst are presented for further understanding. It was possible to characterize the crystalline structure of CNF as herringbone type. Particles derived from a catalyst film of Fe is the focus of our analysis by TEM. The particles studied have chemical composition Fe3C and orthorhombic crystal system. They usually consist on a single crystal obeying a orientation that it seems to have crystallographic relations with the fiber axis. There is evidence that the graphitic sheet arises in particular facets exposed by the particle. Mössbauer Spectroscopy ratifiesthe proposed structure and also shows a small amount of other Iron0sphase, Austenite - -Fe, whose particles were not found on TEM. Finally,EDS showed the chemical composition in a few points of the particle andsome elements, Si and O, seem to involve it. The information obtained provides facts suggesting a possible growth mechanism presented at the end of dissertation.